Laser Techniques for reshaping the Cornea - Aya Ehab Hamdy Jasem; Zahra Ali Hussein Mohammed; Noor Raad Mahawi Mahwish; Baraa Muhammad Asal Saleh (Genius Journals, 2024)
The shape of the cornea of the eye can be modified to correct permanently for nearsightedness or far-sightedness. Heat energy can be delivered to the cornea for this purpose in order to elevate the collagen in mid-cornea to its shrinkage temperature of about 60 °C. When a suitable pattern of shrinkage is created in the peripheral cornea, the central cornea may steepen or flatten in response, and this change in curvature may serve as a refractive correction
Keywords: cornea; Laser Techniques; radiation